Fine-tuning ALK1 linear polyubiquitination to control angiogenesis. Issue 9 (September 2021) - ten Dijke, Peter; Baker, David
Abstract : Editing linear polyubiquitination of protein substrates by LUBAC and OTULIN is known to play a critical role in immune responses. A recent study by Fu et al . reveals how reversible linear polyubiquitination of the activin receptor-like kinase (ALK1) controls developmental angiogenesis and how its dysfunction leads to vascular malformations in humans.